Flouting Maxim in BBC Series “Sherlock: A Study In Pink” - Burhan, Rezuwana (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p29, 2018)
This research entitled “Flouting Maxims in BBC Series “Sherlock A Study In Pink”” aims at investigating the flouting maxims and analyzing the context of situation behind the flouting maxims produced by the character in Sherlock: A Study In pink. Sometimes speaker blatantly and deliberately fails to fulfill the certain maxims because the speaker wants to express the implicit meaning hidden behind the literal meaning. The data was taken from the utterance of the characters in “Sherlock: A Study in Pink”. The observation method is used in collecting the data since the data are obtained from spoken source like movie. The/ method and technique of analyzing data used in this study was descriptive qualitative method. By applying Grice's cooperative principle and his theories on flouting and theory of Context of Situation by Halliday and Hassan (1985), certain conversations show recurring uses of flouts and the reason by context of situation. From the analysis, the most flouted maxim from the collected data is maxim of relation and the least flouted maxim is maxim of quantity and quality. There are several utterances that has flouted more than one maxim. Another point is about the context of situation behind the flouting maxim occurred in the data. There are several context of situation that make the characters flouted the maxim based on the analysis. By knowing the context of situation, the participant can easily conclude the meaning behind the flouting maxim.